Jalan Menuju Taqwa Perspektif Syaikh ‘Abdul Qadir Al-Jailani (Analisis Penafsiran Ayat-ayat Taqwa dalam Tafsir al-Jailani) - Basri Mahmud; Hamzah Hamzah; Muhammad Imran (Institut Agama Islam Negeri (IAIN) Curup, 2022)
The Path to Taqwa from the Shaykh 'Abdul Qadir Al-Jailani’s Perspective: Analysis of the Interpretation of Taqwa Verses in Tafsir al-JailaniThis research focuses on the study of the interpretation of the verses of taqwa in the interpretation of al-Jailani as the culmination of various rituals required by Allah, this research includes descriptive qualitative research, which provides a systematic, careful and accurate description of the interpretation of Shaykh 'Abdul Qadir al-Jailani about the verses of piety. This study uses two data, namely primary data in the form of verses of the Qur'an, namely verses containing taqwa words while secondary data in the form of interpretation of ideas, ideas, other written materials that are related to this research The results of this study show that the terminology of taqwa with its various kinds is repeated 242 times in the Quran. The essence of taqwa according to Shaikh 'Abdul Qadir al-Jailani is obedience built solely to Allah, obeying his commands not violating them, remembering them instead of forgetting them, being grateful for them instead of incarnating them. The devout are those who obey God's commands and spare their souls from all forms of obedience that can hinder true purity and access to closeness to the Creator. The way to attain devotion according to Shaikh Abdul Qadir Jailani is to abstain from the deeds that deeds that deeds that are deeds that deeds of Allah's servants and their rights, escape from obedience, which include great sins and minor sins and then preoccupied oneself with forsaking the sins of the heart which is the mother of various sins and the essence from which it gives birth to sins in the limbs. The sins of the heart such as riya', nifaq, ujub, takabbur, ambition, gluttony, fear of beings, hoping for them, expecting office and position, accentuating themselves to others. The privileges of a devout person according to him are: (1) getting blessings and happiness, (2) getting solutions to the problems he faces and sustenance from God, (3) getting love and protection from God, (4) getting Lessons from God and (5). Get God's forgiveness and heaven